Brain activation during human defensive behaviour: A systematic review and preliminary meta-analysis. (March 2019) - Patrick, Fiona; Kempton, Matthew J.; Marwood, Lindsey; Williams, Steven C.R.; Young, Allan H.; Perkins, Adam M.
Highlights: Systematic review indicates forebrain-to-midbrain move in activation with increasing threat proximity in simple avoidance. Goal-conflict is associated with both subcortical and cortical response. A specific role for the hippocampus was identified in goal-conflict. A preliminary meta-analysis of simple avoidance did not support the review, only showing activation of prefrontal areas. There was a very high level of heterogeneity in available paradigms, which may limit these findings. Abstract: The neural underpinnings of defensive behaviour have implications for both basic research and clinical translation. This review systematically collates published research on neural response during simple avoidance of threat and approach-avoidance behaviour during goal-conflicting situations and presents an exploratory meta-analysis of available whole-brain data. Scopus, PsychInfo and Web of Science databases were searched for the period up to March 2018. 1348 simple avoidance and 1910 goal-conflict publications were initially identified; following review, 8 simple avoidance and 11 goal-conflict studies were included, with 5 datasets used in a preliminary meta-analysis. A move from forebrain-to-midbrain activation as threat becomes more pertinent was noted, indicating support for the Reinforcement Sensitivity Theory of behaviour and general compatibility with animal work. However, these findings were not reflected in the subsequent preliminary meta-analysis. This review highlights the considerable heterogeneity in currently available defensive behaviour paradigms and the lack of research in clinically relevant populations.